Association of Left Atrial Volume Index with Adverse In-Hospital Outcome in Patients with St-Elevated Acute Myocardial Infarction (Bangladesh Heart Journal, 2024)
Background: Coronary heart disease is the leading cause of death worldwide, with acute STEMI being the most severe manifestation. Left atrium (LA) plays a major role in left ventricular performance. LA function is a surrogate marker of LV diastolic dysfunction. In recent past, several studies conducted in different parts in the world have focused on the effect of ASTEMI on the volume and function of left atrium.  So, assessment of left atrial volume index (LAVI) by 2D echocardiography in patients who have suffered an acute STEMI helps to predict the adverse cardiovascular outcome.Objective: The aim of the study is to assess the LAVI for prediction of adverse in-hospital outcomes following acute STEMI patients admitted in a tertiary care hospital.Methods: This Hospital based prospective observational study was conducted in the department of cardiology in DMCH over 1-year period. Patients with acute STEMI admitted in the CCU of DMCH were approached for inclusion in the study. Clinical and echocardiographic parameters were collected within 48 hours of admission. LA volume is measured and then indexed to body surface area called LA volume index (LAVI) and the population was divided according to LAVI. The study comprised of 150 acute STE-MI patients and were divided into two groups, including 75 patients in each group. Patients with LAVI>34 ml/m2and LAVI≤34 ml/m2 were assigned as Group I and Group II respectively & followed up for adverse in-hospital outcome. All necessary information were recorded in a pretested case record form. Statistical analyses were done by SPSS 17.0.Result: The mean age was 57.7 ± 7.0 years ranging from 39 to 80 years. Most of the patients were male 109 (72.7%). Majority of the patients had anterior wall ( anterior, antero-septal & extensive anterior) myocardial infarction (85%).It was observed that patients with LAVI>34 ml/m2(Group I) had more adverse in-hospital outcomes than patients with LAVI≤34 ml/m2( Group II) (46.7% vs 14.7 % ;p< 0.001 ).By multivariate logistic regression analysis, LAVI>34 ml/m2 emerged as an independent significant predictor of adverse in-hospital outcome(Odds Ratio 6.55,95% confidence interval: 2.069 – 20.735, p = 0.001 )Conclusion: In patients with acute STEMI, with LAVI>34 ml/m2 had more adverse in-hospital outcomes than patients with LAVI≤34 ml/m2. So early assessment of LAVI by echocardiography is useful to predict adverse in-hospital outcome.Bangladesh Heart Journal 2024; 39(1): 10-16